2017
DOI: 10.1177/1465116517702004
|View full text |Cite
|
Sign up to set email alerts
|

The European Commission’s use of consultation during policy formulation: The effects of policy characteristics

Abstract: This article asks to what extent the European Commission’s use of consultation depends on policy characteristics of the proposal being formulated. It examines all consultations organized during a formulation process and looks at the number of open consultations (online consultations) as well as the number of repeat consultations (expert groups, policy fora) by the total number of consultations. Three types of use of consultation are conceptualized. A multinomial logistic regression is performed on a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…We found that legal provisions matter for consultation diversity; more precisely, legal rules interact significantly with agency age and the composition of agencies' advisory committees. This corroborates earlier findings on how stakeholder participation, but also access and potential influence, is not only a matter of stakeholders' own incentives to mobilise (so-called supply-side factors) but also shaped by the institutional setting policymakers establish for interactions with stakeholders (so-called demand-side factors) (Mahoney 2004;Kohler-Koch and Finke 2007;Quittkat 2011;Van Ballaert 2017).…”
Section: Resultssupporting
confidence: 89%
“…We found that legal provisions matter for consultation diversity; more precisely, legal rules interact significantly with agency age and the composition of agencies' advisory committees. This corroborates earlier findings on how stakeholder participation, but also access and potential influence, is not only a matter of stakeholders' own incentives to mobilise (so-called supply-side factors) but also shaped by the institutional setting policymakers establish for interactions with stakeholders (so-called demand-side factors) (Mahoney 2004;Kohler-Koch and Finke 2007;Quittkat 2011;Van Ballaert 2017).…”
Section: Resultssupporting
confidence: 89%
“…A third line of reasoning attributes different participation patterns to different consultation institutions that increase or decrease participation costs. Again using the EU as an empirical example, the literature argues the European Commission strategically design consultations to have higher or lower entry costs (Arras and Beyers 2020;Arras and Braun 2018;Bunea and Thomson 2015;Van Ballaert 2017). In that way, they can influence the quantity and type of actors participating, and thereby influence the quantity and type of information they obtain (Broscheid and Coen 2007).…”
Section: Theory: Who Participates In Consultations?mentioning
confidence: 99%
“…In addition to regulation-specific characteristics, we also expect institutional factors to affect the density and diversity of stakeholder mobilization. Consultation tools vary in their degree of openness and hence shape the number and type of stakeholders they filter into the policy system (Pedersen et al 2015; see also Bunea 2017;Rasmussen and Carroll 2013;Van Ballaert 2017). In EU regulatory governance, many approaches involve a combination of open and closed consultation tools, such as online consultation, advisory committees, expert groups and workshops (see Fraussen et al 2020 for a more detailed discussion).…”
Section: Hypothesesmentioning
confidence: 99%